Effects of Different Sowing Schedules and Planting Geometry on Yield and Productivity of Brassica Juncea L. (Bangladesh Journal of Botany, 2022)
A field experiment was conducted to study the effects of different sowing schedules and planting geometry on yield and productivity of Indian mustard (Brassica juncea L.) var. Giriraj. Among the different sowing schedules, sowing mustard crop on 2nd decade of October was found to produce significantly higher seed and biological yield. The early sowing of mustard crop recorded higher values of utilization and accumulation of various agromet indices like growing degree days (GDD), helio-thermal units (HTU) and photo-thermal units (PTU) as well as higher values of photothermal index (PTI) at different phenological stages than other treatments in comparison. Among the planting geometry significant increase in the seed and biological yield was observed in the plots sown with planting geometry of 30 cm × 10 cm which however was found to be at par with 30 cm × 20 cm. The maximum and minimum temperature and thermal indices at vegetative and reproductive stages had a significant correlation on seed yield of mustard crop during the three years of experimentation. Similarly, heat use efficiency was also significantly related with seed and biological yield of mustard.Bangladesh J. Bot. 51(3): 631-635, 2022 (September)